2000
DOI: 10.3349/ymj.2000.41.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Expression of leptin receptor (Ob-R) in human atherosclerotic lesions: potential role in intimal neovascularization

Abstract: Neovascularization of the adventitial vasa vasorum with extension into the intima of atherosclerotic lesions is frequently observed, but its pathophysiological significance is still subject to debate. Recently, leptin, the product of the Ob gene, was identified. Leptin, via activation of the endothelial receptor (Ob-R), generates a growth signal involving a tyrosine kinase-dependent intracellular pathway and promotes angiogenic processes. We hypothesized that a high concentration of leptin within vasa vasorum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 0 publications
2
40
0
Order By: Relevance
“…Our study in healthy adolescents suggests a marked influence of leptin on arterial distensibility. This observation, together with evidence from experimental models [15][16][17][18][19][20] and from prospective studies that show an influence of leptin on clinical outcomes, 32,33 strongly suggests that leptin is one mechanism by which body fatness is linked to the early stages of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study in healthy adolescents suggests a marked influence of leptin on arterial distensibility. This observation, together with evidence from experimental models [15][16][17][18][19][20] and from prospective studies that show an influence of leptin on clinical outcomes, 32,33 strongly suggests that leptin is one mechanism by which body fatness is linked to the early stages of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20] Although predominantly involved in the hypothalamic control of body weight, leptin receptors are widely distributed on endothelial cells, [15][16][17] on other arterial wall subpopulations, 19 and on atherosclerotic lesions. 18,19 An action of leptin via these receptors may stimulate smooth muscle cell proliferation and migration, 20 whereas prolonged treatment with leptin has been shown to increase vascular cell calcification. 19 Leptin has also been shown to induce oxidative stress in endothelial cells, which could contribute to vascular pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, serum leptin concentrations were positively correlated with the periodontal disease progression. It has been suggested that rise in serum leptin concentration acts as a risk factor for cardiovascular diseases as it promotes atherosclerosis by enhancing platelet aggregation, 6 neovascularization of atherogenic plaque, 7 induction of oxidative stress in arterial wall 8 and also acceleration of hepatic degradation and clearance of high density lipoprotein (HDL) apoproteins. 9 Further, it induces calcification of arterial walls, thereby losing elasticity (distensibility), making them stiffer.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin gene expression has been reported in adipocytes, fibroblasts and various other cell types, yet the role of leptin in vascular SMCs is unknown. Leptin receptors have been reported to be widely distributed on endothelial cells [21][22][23] and other arterial wall subpopulations 24) , and in atherosclerotic lesions 24,25) . One action of leptin via these receptors may be to stimulate smooth muscle cell proliferation and migration 26) , whereas prolonged treatment with leptin has been shown to increase vascular cell calcification 24) .…”
Section: Discussionmentioning
confidence: 99%